Integrative natural health solutions for midlife women - Dahia, Vanita; Shannon, Will; Suraev, Anastasia; Villella, Sandra; Münch, Gerald; Chan-Lau, Diana; Hunter, David J. (Frontiers in Nutrition, 2025)
Global interest in natural health products (NHPs) as complementary or alternative treatments is growing, especially among midlife women, due to their diverse health needs. Despite increased NHP use and benefits suggested by traditional use, the available scientific evidence supporting NHP efficacy and safety is often inconsistent, leading to hesitancy among health professionals about their use, even when reasonable evidence exists. Here, we offer a multidisciplinary perspective on optimizing NHP use alongside conventional clinical management in midlife women’s health. We advocate for robust systematic frameworks to generate and evaluate evidence from well-designed clinical studies, employing methodologies like those used for conventional medicines, but adapted to address the unique complexities of NHPs. We highlight key considerations for designing and developing NHP formulations: understanding differences in the activity spectrum of distinct extracts, the bioavailability of active compounds, and the chemical forms of the products. We also emphasize the importance of effectively communicating evidence on NHPs and its implications to health professionals and consumers, so as to maximize therapeutic benefits and minimize potential health risks. Essential actions include incorporating NHP education into continuing education programs for health professionals and enhancing public health literacy to promote safe, responsible, and informed use among consumers. Evidence-based approaches and multidisciplinary collaborations will help drive these essential actions and accelerate the complementary use of NHPs in improving health outcomes.